A new structure of PCHE with embedded PCM for attenuating temperature fluctuations and its performance analysis. (1st September 2022) - Zhang, Lianjie; Yang, Ping; Li, Wei; Klemeš, Jiří Jaromír; Zeng, Min; Wang, Qiuwang
Abstract: The heat exchanger is an essential component of the supercritical CO2 Brayton cycle. To attenuate the temperature fluctuations in the cycle, this study proposes a new structure with phase change materials embedded in the printed circuit heat exchanger. This structure package can contain a variety of phase change materials in a stepwise arrangement and a composite phase change material with expanded graphene. The effects of different flow directions, the number of layers in the phase change material ladder, whether the phase change material is compounded with expanded graphene or not, and the thickness of the phase change material were numerically compared. The results show that the PCM layer with 0.45 mm thickness has a smaller amplitude of both temperature fluctuations and liquid fraction fluctuations than that of 0.25 mm. Relative to the case without PCM, the outlet of hot side' temperature fluctuation amplitude of PCM/EG-3 and PCM/EG-5 with 0.45 mm thickness decreased by 17.11% and 22.37%, and the outlet of cold side' temperature fluctuation amplitude decreased by 36.84% and 38.16%, while the heat exchange decreased by only 2.28% and 1.78%, respectively. Highlights: A new structure for PCM embedded in PCHE is designed. The effects of flow direction on the performance of PCHE-PCM are compared. The effects of a multi-layer PCM ladder arrangement on PCHE-PCM are investigated. The composite structure of PCM/EG significantly reduces the heat loss of PCHE. The effects of different PCM layer thickness on PCHE-PCM are investigated.